Topic delivery of analgesics in oral surgery - Réthoré Gildas; Kimakhe Saïd; Cloitre Alexandra; Weiss Pierre; Lesclous Philippe (EDP Sciences, 2019)
Introduction: Following any oral surgery procedure, postoperative pain is an inevitable outcome and can be described as moderate to severe. The pain management is essential for the comfort and the well-being of the patients. Topical delivery and more specifically transmucosal delivery systems seem to be of great value for the development of new pain management strategies. Method: A systematic literature review was performed using PubMedCentral database. Only PubMedCentral indexed publications were selected and included if they described i) a human clinical study with pharmacokinetic and/or pain relief assessment a biomaterial for topic delivery, ii) the delivery of analgesics or NSAIDs for analgesic purpose and iii) a biomaterial for topic delivery. Results: Ten articles were selected among which 4 pharmacokinetic studies and 8 studies describing pain relief. Six of the selected articles were well defined with a good scientific level of evidence (level 2) and 4 of them with a low level of evidence. Discussion: The clinical investigations demonstrated a good analgesia, a rapid pain relief with a decrease of the administered doses compared to the oral administration. Moreover, these topic analgesics were well tolerated by the patients. Number of devices was developed for the topical delivery after oral surgery procedures. Excepting a gelatin sponge and a hydro alcoholic gel, most of the devices were made of cellulose and its derivatives. Authors reported that the materials showed a good maintenance at the site of application and the release of the analgesic was well controlled over the time. Conclusion: However, well conducted large clinical trials are still missing in order to validate the absence of side effects.